Self-control and its relationship to aggressive behavior among students of the Faculty of Physical Education and Sports Sciences - Matar, Prof. Dr. Shaimaa Abdel; generous, M. D. Gibran is (Sulaimani Journal for Humanities, 2026)
The research aimed to: Identify self-control and aggressive behavior among second-year students at the College of Physical Education and Sports Sciences. Identify the relationship between self-control and aggressive behavior among these students. The research hypotheses were: 1. There are statistically significant differences in self-control and aggressive behavior among second-year students. 2. There are statistically significant differences in self-control and its relationship to aggressive behavior among second-year students. The researchers adopted a descriptive survey methodology, as it was suitable for the research sample, which consisted of second-year students at the College of Physical Education and Sports Sciences. The research sample comprised (70) students. The Self-Control Scale and the Aggressive Behavior Scale were used for the research sample. The scientific basis for these scales, including validity, reliability, and objectivity, was also established. The most important conclusions reached by the researchers are: 1. Students of the College of Physical Education and Sports Sciences possess a good level of self-control. 2. There is a statistically significant relationship between self-esteem and aggressive behavior among the research sample. Therefore, the researchers recommended several measures, including: 1. Attention should be given to educational and psychological counseling within the college, particularly by the deanship, and students' psychological and academic problems should be addressed. 2. Scientific, educational, and recreational programs, activities, and events should be provided that contribute to developing self-control and reducing aggressive behavior.
Keywords: Selfcontrol; aggressive behavior; physical education and sports science students